SIFAT VENIR DAN KAYU LAPIS BEBERAPA JENIS KAYU INDONESIA - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
This report  deals with peeling,  physical  and  mechanical properties  of  veneer and some physicai   and  mechanical properties  of  plywood (triply)  of  16 wood species from  East  Kalimantan  and  1 species from   West  Java.  The logs  of  all wood species tested could  be peeled  without heating or steaming.   Veneer of 0.9 mm  and 1.5 mm  in thickness  could be peeled  at cutting  angles between  89° and 92°.